PENERAPAN COMMUNITY BASED TOURISM DI AIR TERJUN PATI SONI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Septa Hendra; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to implement community based tourism in the tourism object of pati soni waterfall, kuantan mudik subdistrict, kuantan singingi regency. This study uses a qualitative approach with subject of research is the surrounding community that manages tourism object, trades and village UKMs. Data Collection is done by in depth identifying characteristics, identifying elements of tourism systems and developing community based tourism.The results of this study show that Pati Soni Waterfall has potensial of water tourism which is still preserved. But the management is not good enough. The information of community based tourism management is very nesessary. The community must play an active role in providing facilities such as lodging, parking, foods adn drinks, souvenirs and tour guides. So that every tourist who comes can be fulfilled their needs. Keyword : Community Based Tourism, Waterfall, Desa Seberang Cengar